PENGARUH IMPLEMENTASI AI PADA SISTEM INFORMASI PENJUALAN - Hutasoit, Elfhian Goklas Pangihutan; Jhon Kristopel Manalu; Darwis Manalu (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The extremely rapid development of information technology in the era of digital transformation has pushed organizations to continuously adapt to various technological innovations in order to maintain and enhance their competitive advantage. One of the innovations experiencing rapid growth is Artificial Intelligence (AI). The utilization of AI is no longer limited to mere technical aspects but has been widely applied across various organizational functions, including in management information systems. Specifically, AI is increasingly being integrated into sales information systems as a tool to support operations and managerial decision-making. This research aims to conduct an in-depth analysis of the influence of AI implementation on the performance of sales information systems. The research approach used is a literature study, by reviewing and synthesizing various relevant academic sources, such as scientific journals, textbooks, and previous research publications. The results of the literature review indicate that the implementation of AI in sales information systems can improve operational process efficiency, enhance the level of accuracy in sales forecasting, and support faster and more precise decision-making. Furthermore, AI also contributes to improving service quality, customer experience, and levels of customer satisfaction. The implementation of AI is inseparable from a number of challenges and the emergence of risks related to ethics and data security. Therefore, careful planning and managerial strategies are necessary so that the implementation of AI in sales information systems can provide maximum benefits.